Effectiveness of Acupuncture in Dental Surgery: A Randomized, Crossover, Controlled Trial - Maria L.B. Gil; Luide M.R.F. Marinho; Márcio de Moraes; Ronaldo S. Wada; Francisco C. Groppo; Jorge E. Sato; Maria L.R. de Sousa (Medical Association of Pharmacopuncture Institute, 2020)
Objectives: The objective of this crossover clinical study was to evaluate the effectiveness of Energy Regulation with Acupuncture in clinical occurrences in impacted lower third molar surgeries. Methods: The sample consisted of 22 patients with two impacted third molars, in symmetrical position; divided into two groups: Test Group (TG) with Real Energy Regulation Group and Sham Group (SG) with Acupuncture without Energy Regulation function. The extraction was performed 30 days apart. Energy flow (Ryodoraku Method) and energy regulation performed before extraction were measured. Heart Rate (HR) and Blood Pressure (BP) were evaluated before and after energy regulation and after surgery, residual edema was measured by facial measurements (angle of the mandible to tragus (A-T); angle of the mandible to labial commissure (A-LC); angle of the mandible to the wing of the nose (A-WN); angle of the mandible to the corner of the eye (A-CE); angle of the mandible to the chin (A-C); and mouth opening by the interincisal distance, before and after seven days of surgery. To quantify intraoperative bleeding (ml), blood was aspirated along with the saline solution using a portable vacuum pump adaptor. The amount of saline solution used was subtracted from the final amount of aspirated fluid. Results: Mean of bleeding was lower in TG (p = 0.0392). There were significant differences between groups in facial distances: A-LC (p = 0.010), A-WN (p = 0.030) and A-C (p = 0.008). Conclusion: Energy regulation with real acupuncture was effective in reducing postoperative residual edema and intraoperative bleeding.